Teachers' capacity for organizational learning: the effects of school culture and context. Issue 4 (1st October 2016) - Seashore Louis, Karen; Lee, Moosung
ABSTRACT: This paper investigates how key elements of school culture are associated with teachers' capacity to find and act on new information. We analyzed survey data from 3, 579 teachers located in 117 schools which were a randomly selected sample from 9 states in the US. We found that school cultural components such as academic press, student support, and trust and respect among teachers promote teachers' capacity for organizational learning. We also found that the role of teacher professional culture in molding the capacity for organizational learning is critical. In terms of school contexts, we identified that school level (elementary, middle, and high school) was associated with teachers' capacity for organizational learning in 2 different ways. First, as the school level increases, the capacity for organizational learning tends to decrease. Second, as school level increases, the positive relation between reflective dialogue and teachers' capacity for organizational learning is weakened. Implications of these results are discussed.